The silence of colonial melancholy : The Fourie collection of Khoisan ethnologica - Wanless, Ann (My University, 2008)
Between 1916 and 1928 Dr Louis Fourie, Medical Officer for the Protectorate of South West Africa and amateur anthropologist, amassed a collection of some three and a half thousand artefacts, three hundred photographs and diverse documents originating from or concerned with numerous Khoisan groups living in the Protectorate. He gathered this material in the context of a complex process of colonisation of the area, in which he himself was an important player, both in his official capacity and in an unofficial role as anthropological adviser to the Administration. During this period South African legislation and administration continued the process of deprivation and dehumanisation of the Khoisan that had begun during the German occupation of the country. Simultaneously, anthropologists were constructing an identity for the Khoisan which foregrounded their primitiveness. The tensions engendered in those whose work involved a combination of civil service and anthropology were difficult to reconcile, leading to a form of melancholia. The thesis examines the ways in which Fourie’s collection was a response to, and a part of the consolidation of, these parallel paradigms. Fourie moved to King William’s Town in South Africa in 1930, taking the collection with him, removing the objects still further from their original habitats, and minimising the possibility that the archive would one day rest in an institution in the country of its origin. The different parts of the collection moved between the University of the Witwatersrand and a number of museums, at certain times becoming an academic teaching tool for social anthropology and at others being used to provide evidence for a popular view of the Khoisan as the last practitioners of a dying cultural pattern with direct links to the Stone Age. The collection, with its emphasis on artefacts made in the “traditional” way, formed a part of the archive upon which anthropologists and others drew to refine this version of Khoisan identity in subsequent years. At the same time the collection itself was reshaped and re-characterised to fit the dynamics of those archetypes and models. The dissertation establishes the recursive manner in which the collection and colonial constructs of Khoisan identity modified and informed each other as they changed shape and emphasis. It does this through an analysis of the shape and structure of the collection itself. In order to understand better the processes which underlay the making of the Fourie Collection there is a focus on the collector himself and an examination of the long tradition of collecting which legitimised and underpinned his avocation. Fourie used the opportunities offered by his position as Medical Officer and the many contacts he made in the process of his work to gather artefacts, photographs and information. The collection became a colonial artefact in itself. The thesis questions the role played by Fourie’s work in the production of knowledge concerning the Bushmen (as he termed this group). Concomitant with that it explores the recursive nature of the ways in which this collection formed a part of the evidentiary basis for Khoisan identities over a period of decades in the twentieth century as it, in turn, was shaped by prevailing understandings of those identities. A combination of methodologies is used to read the finer points of the processes of the production of knowledge. First the collection is historicised in the biographies of the collector himself and of the collection, following them through the twentieth century as they interact with the worlds of South West African administrative politics, anthropological developments in South Africa and Britain, and the Khoisan of the Protectorate. It then moves to do an ethnography of the collection by dividing it into three components. This allows the use of three different methodologies and bodies of literature that theorise documentary archives, photographs, and collections of objects. A classically ethnographic move is to examine the assemblage in its own terms, expressed in the methods of collecting and ordering the material, to see what it tells us about how Fourie and the subsequent curators of the collections perceived the Khoisan. In order to do so it is necessary to outline the history of the discourses of anthropologists in the first third of the twentieth century, as well as museum practice and discourse in the mid to late twentieth century, questioning them as knowledge and reading them as cultural constructs. Finally, the thesis brings an archival lens to bear on the collection, and explores the implications of processing the collection as a historical archive as opposed to an ethnographic record of material culture. In order to do this I establish at the outset that the entire collection formed an archive. All its components hold knowledge and need to be read in relation to each other, so that it is important not to isolate, for example, the artefacts from the documents and the photographs because any interpretation of the collection would then be incomplete. Archive theories help problematise the assumption that museum ethnographic collections serve as simple records of a vanished or vanishing lifestyle. These methodologies provide the materials and insights which enable readings of the collection both along and across the grain, processes which draw attention to the cultures of collecting and categorising which lie at the base of many ethnographic collections found in museums today. In addition to being an expression of his melancholy, Fourie’s avocation was very much a part of the process of creating an identity for himself and his fellow colonists. A close reading of the documents reveals that he was constantly confronted with the disastrous effects of colonisation on the Khoisan, but did not do anything about the fundamental cause. On the contrary, he took part in the Administration’s policy-making processes. The thesis tentatively suggests that his avocation became an act of redemption. If he could not save the people (medically or politically), he would create a collection that would save them metonymically. Ironically those who encountered the collection after it left his hands used it to screen out what few hints there were of colonisation. Finally the study leads to the conclusion that the processes of making and institutionalising this archive formed an important part of the creation of the body of ethnography upon which academic and popular perceptions of Khoisan identity have been based over a period of many decades.
Keywords: archives; collecting; colonial history; Fourie, Dr Louis; Khoisan identity; knowledge production; material culture; museum collections; Namibia; photography; physical anthropology; South West Africa Protectorate; ≠Ao-//ein; Hei-//om; Naron